On Becoming Virtuous. (December 2019) - Eriksen, Matthew; Cooper, Kevin; Miccolis, Anthony
Based on Ben Franklin's project to develop his virtuousness, we present an assignment that provides a structured process to facilitate students' virtuousness in their day-to-day lives. Students determine four virtues they wish to develop. Each week, students focus on behaving consistently with one of these virtues. At the end of each day, they record whether their behaviors were consistent with each of their four virtues. On a weekly basis, students engage in self-reflection, practical reflexivity, peer coaching, and a class discussion of their experiences of attempting to live out their chosen virtues and what they are learning about being virtuous, and with what actions and structures they might experiment to improve their effectiveness. These practices deepen students' self-understanding and improve their abilities to be virtuous. Student feedback strongly supports that engaging in the assignment helped them identify meaningful virtues and personal behaviors consistent, and inconsistent, with those virtues, improve their abilities to behave consistently with these virtues, understand the impact of living out their virtues within the context of their day-to-day lives, increase their self-understanding, and improve their abilities to engage in self-observation and self-reflection.